2020
DOI: 10.3390/ijerph17030689
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers, Microbiome, Depression, and Executive Dysfunction in Alcohol Users

Abstract: Alcohol-related disorders (ARD) are highly prevalent among Latin American-Caribbean countries. Mental disorders are common comorbidities in individuals with ARD. However, the etiology of the association between ARD and mental disorders remains unclear. We examined the association of inflammatory cytokines, microbiome, and other biomakers with measures of depression, social anxiety, and executive functions. We observed a significant increase in cytokine and chemokine expression levels in saliva and plasma in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…The exact molecular mechanisms by which alcohol intake act in the subgingival microbial ecotype are not yet clear. Recently, studies investigating mouthwash 12 , 42 and salivary 43 samples identified features of a dysbiotic community such as decreased abundance of commensals, overall loss of diversity and enriched pathogenic taxa in heavy drinkers. The increased proportions of specific periodontal pathogens caused by ethanol are possibly a result of the decreased commensals (i.e, Lactobacillales , Streptococcus and Rothia ) levels 12 , 44 and/or inflammation-related disturbances (which are expected to act on periodontal pocketing) associated with the immune subversion on the gingival crevicular fluid, ultimately impairing the host-microbial balance.…”
Section: Discussionmentioning
confidence: 99%
“…The exact molecular mechanisms by which alcohol intake act in the subgingival microbial ecotype are not yet clear. Recently, studies investigating mouthwash 12 , 42 and salivary 43 samples identified features of a dysbiotic community such as decreased abundance of commensals, overall loss of diversity and enriched pathogenic taxa in heavy drinkers. The increased proportions of specific periodontal pathogens caused by ethanol are possibly a result of the decreased commensals (i.e, Lactobacillales , Streptococcus and Rothia ) levels 12 , 44 and/or inflammation-related disturbances (which are expected to act on periodontal pocketing) associated with the immune subversion on the gingival crevicular fluid, ultimately impairing the host-microbial balance.…”
Section: Discussionmentioning
confidence: 99%
“…Using the method outlined by Rodrguez-Rabassa et al . [ 16 ] and Zapała et al .,[ 17 ] the core microbiome assessment of a taxonomic cluster that represented a sizable fraction of the population and a comparative analysis of the microbiome within and between the groups was examined.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…As mentioned before, excitotoxicity results in neuronal degeneration and neuroinflammation, in which such disturbances have been widely reported in depression pathology [ 108 , 146 , 148 , 149 ]. Indeed, depression symptomatology has been associated with cytokine and chemokine expression levels’ upregulation in the saliva and plasma of individuals that consumed ethanol, as well as dysbiosis of salivary microbiota [ 156 ]. Furthermore, a degenerative process provoked by excitotoxicity is accompanied by mitochondrial damage, release of superoxide radicals, lipid peroxidation, and other mechanisms linked to oxidative stress [ 147 , 150 ].…”
Section: Body Systems Consequences Of Ketamine Plus Ethanol Abusementioning
confidence: 99%